Lightkeeping on the St. Lawrence : the end of an era - Lafrenière, Normand (Dundurn Press, 1996)
Lightkeeping on the St. Lawrence outlines the history of lightkeeping in the St. Lawrence River and Gulf from its emergence in 1803 until automation replaced the last lightkeeper in 1988. Fog, hidden reefs, rocks, and sandbars have made the waters of the river and gulf among the most treacherous in the world. In the earliest days of lightkeeping in this region, the safety of the mariners had to be weighed against the problem of giving aid to enemy ships. With peace between French and English, safety became the overriding factor and the number of lighthouses, then light pillars and lightships.